Immune response to progesterone immobilized on Cu2+- induced amphifilic polyelectrolyte-protein complex: Antigen specificity and affinity of hybridoma clones - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 2001)
Cu2+-mediated complex formation between copolymers of acrylic acid with N-isopropyl-acyrlamide (CP1) and negatively charged covalent conjugate of bovine serum albumin with progesterone (BSA.P) was studied in neutral water in the presence of Cu2+. If was shown that under conditions where CP and BSA.P are negatively charged and incapable of binding to one another, the divalent Cu2+ act as fasteners promoting the formation of relatively stable water-soluble ternary polycomplexes, The immunogenic properties of ternary mixtures BSA.P-Cu2+-CP1 and BSA.P+IFA were investigated and the production of monoclonal antibodies (MAbs) against progesterone hormone was analyzed. Fusion following the two different immunization procedures resulted in the growth of comparable numbers of progesterone-specific MAbs with apparently similar antigen affinities. Thus, immunizations using antigens in BSA.P-Cu2+-CP1 appear to provide an efficient alternative to incomplete Freund's adjuvant.
Keywords: BOVINE SERUM-ALBUMIN; AMPHIPHILIC IMMUNOGENS; MONOCLONAL-ANTIBODIES